Near-infrared molecular fieldoscopy of water - Alismail, Ayman; Wang, Haochuan; Barbiero, Gaia; Hussain, Syed Ali; Schweinberger, Wolfgang; Krausz, Ferenc; Fattahi, Hanieh (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2019)
We introduce the concept of broadband near-infrared molecular fieldoscopy. In this scheme, molecules are excited by femtosecond pulses in near-infrared spectral range and the complex electric field of their free induction decay is directly measured by means of electro-optic sampling. Few-cycle pulses centered at 2 μm and 1 μm are generated from a 5 kHz, Yb:YAG regenerative amplifier and employed for femtosecond excitation and electro-optic sampling, respectively. We chose water in an acetic acid solvent to demonstrate the first proof of principle measurement with the novel technique. The complex electric field of the combination bond of water molecules at 1930 nm at different molecular concentrations is detected and presented. We show the detection sensitivity of our time- domain technique is comparable to conventional specral-domain techniques. However, by employing a laser frontend with higher repetition rates, the detection sensitivity can be drastically enhanced. To the best of our knowledge, this is the first detection of the complex electric field of the molecular response in near-infrared spectral range. The new method holds promise for high-resolution overtone spectroscopy and microscopy with unparalleled sensitivity and specificity over the entire molecular fingerprint region.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Background-free detection; Femtosecond fieldoscopy; Femtosecond laser sources; Femtosecond spectroscopy; Near-infrared spectroscopy; Overtone excitation; Time-domain spectroscopy; Water; Yb:YAG lasers